Cango Cave, Oudtshoorn District of the Cape Province, South Africa : an assessment of its development and management 1780-1992 : short title, Management problems at Cango Cave - Craven, Stephen Adrian (Department of Environmental and Geographical Science, 2016)
Includes bibliographical references.